2020
DOI: 10.3174/ajnr.a6875
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Determination of IDH and 1p19q Status of Lower-grade Gliomas Using MRI Radiomics: A Systematic Review

Abstract: BACKGROUND: Determination of isocitrate dehydrogenase (IDH) status and, if IDH-mutant, assessing 1p19q codeletion are an important component of diagnosis of World Health Organization grades II/III or lower-grade gliomas. This has led to research into noninvasively correlating imaging features ("radiomics") with genetic status. PURPOSE: Our aim was to perform a diagnostic test accuracy systematic review for classifying IDH and 1p19q status using MR imaging radiomics, to provide future directions for integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 57 publications
(133 reference statements)
1
41
0
Order By: Relevance
“…Other studies try to predict 1p/19q status, some of which aim to solve the same problem using MRI [15][16][17][18][19][20][21][22]. They all are using multimodal conventional MRI data, most often combining T2-weighted and contrast enhanced T1-weighted data together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies try to predict 1p/19q status, some of which aim to solve the same problem using MRI [15][16][17][18][19][20][21][22]. They all are using multimodal conventional MRI data, most often combining T2-weighted and contrast enhanced T1-weighted data together.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years different studies have demonstrated that 1p19q status can be predicted using MRI [15][16][17][18][19][20][21][22]. Furthermore, Branzoli et al [23] recently identified elevated levels of cystathionine in 1p/19q codeleted gliomas compared to non-codeleted gliomas, using in vivo magnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as recently suggested by Bhandari et al, a greater effort is needed to start translating these findings into an interpretable format for clinical radiology [ 89 ]. In addition, as several studies focused on singular molecular biomarkers in gliomas, it must be underlined several molecular alterations in astrocytic, oligodendroglial gliomas can occur in different combinations [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the T2-FLAIR mismatch sign has been shown to predict astrocytoma, IDH-mutant with 95-100% speci city [14,15]; however, sensitivity has been low at 46-51% [8, 14, 16]. Inter-rater agreement has been shown to have a wide range of κ = 0.38-0.88 [5,8,14,15].…”
Section: Discussionmentioning
confidence: 99%